2022
DOI: 10.24996/ijs.2022.63.5.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Urban Expansion Indices Change by (R.S.) on Height of Convective Radix Layer around Baghdad Airport (Iraq)

Abstract: Change in structure of land surface can affect atmospheric boundary layer and formation of internal boundary layer. This will change shear stresses and turbulent boundary layer. Change in low level wind shear and turbulent can affect air craft performance and has potentially adverse effects on flight safety during landing and taking-off stages. In this study, change in land area around Baghdad Airport and its effects on structure of boundary layer and radix layer through summer season (July from years 1985 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…There is large difference in sensible heat flux in watt/m 2 at 5 Jan. and 5 July through 12PM, over Baghdad province, this will change vertical flux at two cases, and change wind speed (9). 8) show the observed cases of horizontal wind speed with altitude plotted during 6 days at January and July from 2014, the observed case on 1-January was not plotted in (Figure 8a,b), but this case is analysis and represent in all conclusion.…”
Section: Atmospheric Upper Layer Conditionsmentioning
confidence: 99%
“…There is large difference in sensible heat flux in watt/m 2 at 5 Jan. and 5 July through 12PM, over Baghdad province, this will change vertical flux at two cases, and change wind speed (9). 8) show the observed cases of horizontal wind speed with altitude plotted during 6 days at January and July from 2014, the observed case on 1-January was not plotted in (Figure 8a,b), but this case is analysis and represent in all conclusion.…”
Section: Atmospheric Upper Layer Conditionsmentioning
confidence: 99%
“… The extinction of many living organisms. Studies indicate that extreme weather, especially high temperatures, will lead to an increase in death rates in the future [11], and an increase in temperatures near the surface of the earth will rise to higher levels and cause additional disturbances except for the natural disturbance resulting from wind shear and friction, which leads to an impact on the safety of air navigation near airports at take-off and landing [12]. One of the studies relied on monthly temperature data for the period (2003-2016) for different stations covering Iraq and showed that the average temperature throughout Iraq increased by (1 o C) at the end of the study period [13].…”
Section: Previous Related Studies In Iraqmentioning
confidence: 99%